ANALISA KINERJA SISTEM INFORMASI MANAJEMEN ASET PADA PT. PRECISE PACIFIC REALTY MENGGUNAKAN METODE BALANCED SCORECARD - Ni Putu Widi Astuti, Ni Putu Widi Astuti (Jurnal Sistem Informasi Akuntansi (JASIKA), 2024)
In an increasingly developing business world, technology plays an important role in presenting new ideas in all fields. Supporting information can be in the form of programs or applications for marketing or finance and accounting. Asset management information system (SIMA) is an approach that involves the use of information technology to efficiently and effectively manage a company's assets. An asset can include things such as equipment, property, intellectual property, or other resources that have economic value. Therefore, researchers are interested in analyzing the performance of asset management information systems using the Balanced Scorecard method, which has 4 perspectives for assessing. To obtain research data results, use a questionnaire to distribute with the help of Google Form. The results of the answers will be recorded, processed and clarified using Tableau and Microsoft Excel 2019 software. Tableau itself is an imaginative and interactive data visualization software. The company is guaranteed to exude performance not only focusing on the financial aspect, but also covering the perspective of user satisfaction, producing services with innovations in the internal process perspective, as well as learning and growth perspectives such as motivating employees to achieve competitive advantage in asset management.